Thematic Analysis Approach: A Step by Step Guide for ELT Research Practitioners - Dawadi, Saraswati (Journal of NELTA, 2020)
The author, having drawn examples from her doctoral study, describes how a thematic analysis approach was employed to interpret raw data in her doctoral study which explored the impacts of a high-stakes test on students and parents in Nepal. As the main purpose of this paper is to provide some guidelines for English language teaching (ELT) practitioners and early career researchers to rigorously apply a thematic analysis approach, this paper presents a step-by-step guideline for the application of the approach. It also presents detailed examples of the processes the author followed during the analysis of her data (from familiarising with the data to identifying initial codes to preparing a fi nal report) to reveal how analysis of the raw data (from interviews and oral diaries transcripts) progressed towards the identifi cation of overarching themes that captured the nature of the test impacts in the Nepalese context described by participants in the study.